FILMINESS IN A BIOGRAPHICAL NOVEL - Žilka, Tibor (Bohemica Olomucensia, 2020)
The study is focused on the identification of artistic and aesthetic values of the biographical novel Gen. M. R. Štefánik (2018) written by Mariana Čengel Solčanská. The author is a well-known director of several successful movies such as Únos (Kidnapping, 2017) and Sviňa (Scumbag, 2019). In her novel about an important Slovak politician and astronomer, she was also able to apply the strategies distinctive for film art. The novel is characterized by increased drama and a constant alternation of mini-stories, ending with a point. These features of the prose text are reminiscent of editing and montage from film art, which makes the novel an excellent reading. The narrator of the story also helps - the entire story of Štefánik's life is told by Eduard Beneš, the future president of Czechoslovakia. This way, the author significantly shifted the plot to a fictitious position.
Keywords: biographical novel; director; narrator; film editing; film montage; mini-story; general; fictional interview